Beyond maintenance: Emerging discourses on waterway renewal in the Netherlands. (December 2018) - Willems, Jannes J.
Abstract: Across the western world, ageing waterworks have to be renewed, but interpretations on transport policies for renewal differ and are indistinct. Our aim is to grasp the competing discourses on the public management of Dutch waterway renewal in order to understand the different interpretations and how these influence waterway planning. The analysis demonstrates that a technical discourse, in which renewal is framed as sustaining the waterway network, currently prevails in the Netherlands. However, this discourse is increasingly complemented by a financial and functional discourse. These new discourses emphasise co-financing arrangements between public governments and the incorporation of new functionalities and trends into the outmoded waterways. As recent practices are altered by the new discourses, the established technical discourse decreases in importance, as does the central role for infrastructure operators. Instead, renewal becomes a strategic, political matter for transport policymakers, in which new waterway configurations are discussed. For producing legitimate future renewal practices, this article recommends that the connection between strategic policymakers and apolitical operators could be improved. Highlights: Infrastructure planning is increasingly faced with the renewal of ageing waterworks. Renewal practices are conditioned by discourses that strive for influence. Prevailing views in our case study reveal a dominant engineering-driven discourse. Currently, renewal does not involve discussing alternative functional requirements. Renewal requires stronger ties between policymakers and apolitical infra-operators.